The Relationship Between the Attitudes of Midwifery Students Towards Euthanasia and Their Religious Attitudes: A Cross Sectional Study in Türkiye - Yüksekol, Özlem Doğan; Koç, Özlem; Baltacı, Nazlı; Polat, Habibe (Ordu University, 2023)
Objective: This study was carried out to determine the relationship between the attitudes of midwifery students about euthanasia and their religious attitudes. Methods: The universe of this cross-sectional study consisted of students studying in the midwifery department of a university in eastern Türkiye. The study was carried out with 284 volunteer midwifery students between November and December 2021. Descriptive statistics such as frequency, percentage, mean and standard deviation values were used in the evaluation of the data. Independent samples t-test and one-way analysis of variance (ANOVA) were used for normally distributed variables, and Spearman correlation analysis was used for non-normally distributed variables. The study data were collected through Google Form. Participants were asked a consent question via the Google form to confirm whether they wanted to participate in the study. Results: The mean total Health Professional Euthanasia Attitude Scale (HPEAS) score of the participants was found as 83.04±16.07, while their mean total Ok-Religious Attitude Scale (ORASI) score was determined as 34.01±6.00. Accordingly, the participants had moderate attitudes about supporting euthanasia, while their religious attitudes were positive. Conclusions: As a result of this study, it was observed that most of the students had negative attitudes towards euthanasia, and one of the factors that affected these attitudes was religious belief.

Amaç: Bu araştırma, ebelik öğrencilerinin ötenaziye yönelik tutumları ile dini tutumları arasındaki ilişkiyi belirlemek amacıyla yapıldı. Yöntem: Kesitsel nitelikte yapılan bu araştırmanın evrenini, Türkiye'nin doğusunda bir üniversitenin ebelik bölümünde öğrenim gören öğrenciler oluşturmuştur. Araştırma, Kasım-Aralık 2021 tarihleri arasında 284 gönüllü ebelik öğrencisi ile gerçekleştirildi. Verilerin değerlendirilmesinde frekans, yüzde, ortalama ve standart sapma değerleri gibi tanımlayıcı istatistikler kullanıldı. Normal dağılım gösteren değişkenler için bağımsız örneklem t testi ve tek yönlü varyans analizi (ANOVA), normal dağılım göstermeyen değişkenler için Spearman korelasyon analizi kullanıldı. Araştırma verileri Google form ile toplandı. Katılımcıların, araştırmaya katılmak isteyip istemediklerini teyit etmek için Google formu ile kendilerine bir onam sorusu soruldu. Bulgular: Katılımcıların Sağlık Profesyoneli Ötenazi Tutum Ölçeği (SP-ÖTÖ) toplam puanı 83.04±16.07 olarak bulunurken, Ok-Dini Tutum Ölçeği (Ok-DTÖ) toplam puanı 34.01±6.00 olarak belirlendi. Puan ortalamalarına göre, katılımcıların ötenaziyi desteklemeye yönelik tutumları orta düzeydeyken, dini tutumları olumluydu. Sonuç: Bu çalışma sonucunda öğrencilerin çoğunun ötenaziye yönelik olumsuz tutumlara sahip olduğu ve bu tutumları etkileyen faktörlerden birinin de dini inanç olduğu görüldü.
Ebelik Bölümü Öğrencilerinin Ötenaziye Karşı Tutumlarının Dini Tutumları ile İlişkisi: Türkiye’de Kesitsel Bir Çalışma
Keywords: Nursing; Hemşirelik